Humour, Transcendence, and Selfhood: An Essay on Lightness and Truth - Ravenscroft, Simon (Modern theology, 2025)
This article is concerned with a ‘lightness that is as far as possible from triviality’. It argues, firstly, that a connection can be drawn between comic perception and pictures of reality that entail transcendence, understood as an otherness at the heart of things that may be indirectly glimpsed but never fully grasped as the object of fixed knowledge. To picture transcendence as enigmatically near within immanence, rather than set abstractly over against it, introduces a sense of relativity and ambivalence into experience. This yields a comic lightness which is nonetheless philosophically serious because it has to do with truth. This has implications, secondly, for understanding selfhood. The essay looks at three accounts of transcendence in this context: the arguments of Socrates regarding the divine madness of eros in Plato's Phaedrus; the development of a more radical conception of transcendence via biblical sources in Philo and Augustine; and the application, via a reconceived Cartesian cogito, of a more moderated account of transcendence in the philosophy of Maurice Merleau-Ponty to the themes of self-knowledge and sincerity. In all cases, the affirmation of transcendence destabilises the ‘mundane’ world and human knowledge of it, and relocates the subject's centre of gravity outside themselves via a characteristic movement of release. In all of them, to grow towards truth requires a renunciation of self-possession and secure self-knowledge: the self must give itself over to transcendent otherness if it is to become what it more truly is. Both world and self increase in mystery in these different renditions, and this is where humour and lightness break in. The realisation of this mysteriousness is not a cause for despair, however, but the means by which one is freed from illusory claims to absolute knowledge (whether of world or self), and journeys towards truth, held now more lightly and with a greater sense of wonder.